Critical issues in human rights and development - Marks, Stephen P.; Rajagopal, Balakrishnan (Edward Elgar Publishing, 2021)
"This collection addresses human rights and development for researchers, policymakers and activists at a time of major challenges. 'Critical issues' in the title signifies both the urgency of the issues and the need for critical rethinking. After exploring the overarching issues of development and economic theory, gender, climate change and disability, the book focuses on issues of technology and trade, education and information, water and sanitation, and work, health, housing and food. The chapters then examine how to operationalize human rights in development through accountability, the right to development, indicators and the Sustainable Development Goals. The conclusion proposes international standards and social mobilization for human rights and sustainable development as normative and policy-oriented tools for addressing the climate emergency, the coronavirus pandemic, social inequality, racial injustice, and the rise of populist authoritarianism and for advancing social justice and the equal value of all human beings. This book is of interest to students of development and human rights studies, international relations, international law and contemporary social issues, as well as professionals working at government, intergovernmental and civil society organizations dealing with these issues"--